2010
DOI: 10.1002/cncr.25127
|View full text |Cite
|
Sign up to set email alerts
|

Ethnicity and management of colon cancer in New Zealand

Abstract: BACKGROUND: Racial and ethnic inequalities in colon cancer treatment have been reported in the United States but not elsewhere. The authors of this report compared cancer treatment in a nationally representative cohort of Maori (indigenous) and non-Maori New Zealanders with colon cancer. METHODS: On the basis of cancer registry data, 301 Maori patients and 329 randomly selected non-Maori patients were identified who were diagnosed with colon cancer between 1996 and 2003. Medical notes were reviewed, and surgic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
35
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 65 publications
(40 citation statements)
references
References 36 publications
3
35
2
Order By: Relevance
“…However after adjustment for all available factors, those using mental health services had worse survival than those without a history of mental health service use (although the differences were for the most part no longer statistically significant), and some of this remaining unexplained survival disadvantage may relate to differences in treatment. While secondary care, including mental health and cancer care, is universally available free of charge in New Zealand's public system, evidence of differences in treatment receipt by ethnicity [33], as well as reports of experience of discrimination by health services from people with experience of mental illness [31], suggests that treatment receipt may be a factor in the survival differences found.…”
Section: Discussionmentioning
confidence: 99%
“…However after adjustment for all available factors, those using mental health services had worse survival than those without a history of mental health service use (although the differences were for the most part no longer statistically significant), and some of this remaining unexplained survival disadvantage may relate to differences in treatment. While secondary care, including mental health and cancer care, is universally available free of charge in New Zealand's public system, evidence of differences in treatment receipt by ethnicity [33], as well as reports of experience of discrimination by health services from people with experience of mental illness [31], suggests that treatment receipt may be a factor in the survival differences found.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, delays in receipt of treatment could be an important contributor to ethnic disparities in survival among NZ women. Longer delays from diagnosis to treatment have been shown for Māori compared to non-Māori for colon and lung cancers in NZ (Hill et al 2010;Stevens et al 2008).…”
Section: Introductionmentioning
confidence: 98%
“…What is known is that there are disparities in cancer survival in New Zealand that are not accounted for by stage at diagnosis 25 and that access through secondary care, rurality and cultural factors may all contribute to less than optimal healthcare. 26,27 The risk of dying from some cancers may be increased at a distance from a tertiary cancer centre, and with worsening socio-economic status. 28 It has been suggested that it is small incremental differences along the cancer pathway that add up to the overall disparity between Māori and non-Māori survival rates.…”
Section: Discussionmentioning
confidence: 99%
“…28 It has been suggested that it is small incremental differences along the cancer pathway that add up to the overall disparity between Māori and non-Māori survival rates. 26 The specialised, episodic, emergency care that ED nurses are trained to provide to a very diverse population 29 does not always meet the needs of this highly specific patient group. 2 Pressure to meet imposed targets such as the ''6 h target'' described by participants and the urgent nature of the ED environment may not serve complexity well.…”
Section: Discussionmentioning
confidence: 99%